Single Physical Performance Measures Cannot Identify Geriatric Outpatients with Sarcopenia - Looijaard, S. M. L. M. (J Frailty Aging, 2018)
BACKGROUND: Sarcopenia is highly prevalent in the older population and is associated with several adverse health outcomes. Equipment to measure muscle mass and muscle strength to diagnose sarcopenia is often unavailable in clinical practice due to the related expenses while an easy physical performance measure to identify individuals who could potentially have sarcopenia is lacking. OBJECTIVES: This study aimed to assess the association between physical performance measures and definitions of sarcopenia in a clinically relevant population of geriatric outpatients. DESIGN, SETTING AND PARTICIPANTS: A cross-sectional study was conducted, consisting of 140 community-dwelling older adults that were referred to a geriatric outpatient clinic. No exclusion criteria were applied. MEASUREMENTS: Physical performance measures included balance tests (sideby- side, semi-tandem and tandem test with eyes open and -closed), four-meter walk test, timed up and go test, chair stand test, handgrip strength and two subjective questions on mobility. Direct segmental multi-frequency bioelectrical impedance analysis was used to measure muscle mass. Five commonly used definitions of sarcopenia were applied. Diagnostic accuracy was determined by sensitivity, specificity and area under the curve. RESULTS: Physical performance measures, i.e. side-by-side test, tandem test, chair stand test and handgrip strength, were associated with at least one definition of sarcopenia. Diagnostic accuracy of these physical performance measures was poor. CONCLUSIONS: Single physical performance measures could not identify older individuals with sarcopenia, according to five different definitions of sarcopenia.